Peran HAM dalam mewujudkan masyarakat yang adil dan sejahtera - arviansyah, ahmad dimas (Maliki Interdisciplinary Journal, 2026)
This research examines how human rights contribute to the establishment of a fair and thriving society. Human rights are essential entitlements inherent to every individual from birth that should be acknowledged, safeguarded, and promoted within both social and governmental contexts. The goal of this research is to explore the significance of human rights in fostering social equity, enhancing public well-being, and sustaining a balanced and democratic community. A qualitative descriptive approach is utilized for this study, incorporating literature reviews from diverse resources such as books, journals, legal documents, and scholarly articles pertinent to human rights. Findings from the research reveal that human rights are crucial in fostering equal rights, ensuring legal safeguards, promoting freedom of speech, and providing equal chances for all individuals without bias. The promotion of human rights also has a positive impact on the advancement of public welfare through the realization of economic, social, cultural, educational, health, and environmental rights. Upholding human rights can bolster democratic principles, establish social and political stability, and enhance mutual respect among community members. Consequently, the recognition and implementation of human rights need to be continually enhanced to foster a just, secure, peaceful, and prosperous society in line with the aspirations of the Indonesian people.